Activated clay and cocoa nib shells-integrated polyvinyl alcohol membranes for fouling mitigation in water treatment - Elikplim Nyabi; Roland Tsoeke Agbetsi; Gideon Addai; Francis Opoku; Mandela Toku; Ray Bright Voegborlo; Eric Selorm Agorku (Next Sustainability)
In this study, an innovative membrane engineering strategy combining polyvinyl alcohol (PVA) crosslinked with formaldehyde and reinforced with varying amounts of activated clay (AC) and cocoa nib shells (CNS) was used to fabricate ultrafiltration membranes for methylene blue (MB) dye removal. Characterization techniques such as zeta potential (ZP), 1HNMR, FTIR, SEM-EDS and XRD were used to verify the successful fabrication of these composite membranes. The synergy between AC’s surface charge modulation and CNS’s microstructural enhancement creates a dual-function mechanism of Donnan exclusion and size-sieving, which significantly boosts separation efficiency and antifouling performance. Composite membrane, MAC3.0/CNS3.0 achieved a porosity of 68 % and a pure water flux (PWF) of 71 L/m2h, outperforming pristine PVA membrane (MPVA), which showed 52.1 % porosity and 55.4 L/m2h flux. The addition of 4.3 wt% of each filler yielded a 30.3 % increase in porosity and a 28.1 % improvement in PWF. Dye rejection reached 95.7 % for MAC3.0/OM3.0. While the flux recovery ratio (FRR) rose from 70.4 % (MPVA) to 89.8 % (MAC3.0/CNS3.0), indicating superior antifouling properties. This work provides a sustainable, low-cost and scalable membrane modification pathway for high-efficiency dye wastewater treatment.